The effect of crystallographic orientation and solution aging on the electrical properties of sol-gel derived Pb(Zr0.45Ti0.55)O3 thin films - Alkoy, Ebru Mensur; Alkoy, Sedat; Shiosaki, Tadashi (Elsevier Sci Ltd, 2007)
Lead zirconate titanate-Pb(Zr0.45Ti0.55)O-3 thin films are grown on Pt-< 1 1 1 >/Ti/SiO2/Si-< 1 (0 0 >) substrates by a sol-gel method with < 1 0 0 >/< 0 0 1 > and < 1 1 1 > preferred orientations. Film orientation was controlled mainly by the annealing process and temperature. Films with < 10 0 >/< 0 0 1 > orientation consist of a uniform microstructure with micron size grains, whereas films with (1 1 1) orientation contain sub-micron grains. The electrical properties were influenced markedly by the microstructure and orientation of the films. The (1 1 1) oriented films exhibit a square-like hysteresis loop with remnant polarization (P-r) reaching 46 mu C/cm(2) under 550 kV/cm, whereas < 10 0 >/< 0 0 1 > oriented films have a P, of 20 mu C/ cm(2) with more slim hysteresis curves. Aging of the precursor solutions resulted in films growing with < 10 0 >/< 0 0 1 > texture and displaying inferior electrical properties. (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: sol-gel processes; ferroelectric properties; PZT; thin films